2019
DOI: 10.31550/1727-2378-2019-162-7-36-39
|View full text |Cite
|
Sign up to set email alerts
|

The Pathogenic Role of Vitamin D in Pelvic Pain Associated with External Genital Endometriosis

Abstract: Цель исследования: расширить представления о патогенезе тазовой боли (ТБ) при наружном генитальном эндометриозе (НГЭ). Дизайн: когортное проспективное сравнительное морфологическое исследование. Материалы и методы. В исследовании приняли участие 150 женщин. Пациенток с НГЭ (n = 120) разделили на 2 группы с 2 подгруппами (А и B) в каждой. Участницы групп I и II были в возрасте от 20 лет до 41 года (средний возраст-29,1 ± 3,3 года). I группу (n = 60) составили пациентки с НГЭ, осложненным ТБ: IA (n = 30)-c дефиц… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…According to domestic and foreign sources, the role of vitamin D, as a necessary component of a wide range of physiological processes and the optimal state of metabolic homeostasis has been established during largescale scientifi c research [7,9]. Vitamin D defi ciency have been proved to be involved in maintaining immune homeostasis, playing an important role in the polymorphism of enzymes in the pathogenetic chain of chronic infl ammation [6,8,9]. Chronic infl ammatory processes are accompanied by excess production of the activated immune system, primarily its mononuclear phagocytic link, and various infl ammatory proteins [6].…”
Section: ключові слова: ендометріоз яєчника запальні захворювання орг...mentioning
confidence: 99%
See 2 more Smart Citations
“…According to domestic and foreign sources, the role of vitamin D, as a necessary component of a wide range of physiological processes and the optimal state of metabolic homeostasis has been established during largescale scientifi c research [7,9]. Vitamin D defi ciency have been proved to be involved in maintaining immune homeostasis, playing an important role in the polymorphism of enzymes in the pathogenetic chain of chronic infl ammation [6,8,9]. Chronic infl ammatory processes are accompanied by excess production of the activated immune system, primarily its mononuclear phagocytic link, and various infl ammatory proteins [6].…”
Section: ключові слова: ендометріоз яєчника запальні захворювання орг...mentioning
confidence: 99%
“…In contrast to acute infl ammatory response, when the secretion of such proteins increases tens to hundreds of times, it increases only 5-6 times in case of chronic infl ammatory systemic response. The literature presents results of epidemiological studies, which reveal an inverse relationship between levels of 25(OH)D3 and infl ammation markers-C-reactive protein and interleukin (IL)6 [8,9]; several in vitro studies have shown that calcitriol inhibits infl ammation in adipose tissue [3,6]. The idea of vitamin D effect on the development and progression of endometriosis, modulating the proliferative mechanisms of endometrial cells in the abdominal cavity, was fi rst expressed by Italian scientists [9].…”
Section: ключові слова: ендометріоз яєчника запальні захворювання орг...mentioning
confidence: 99%
See 1 more Smart Citation